2021
DOI: 10.1186/s13027-021-00354-7
|View full text |Cite
|
Sign up to set email alerts
|

A 12-year retrospective evaluation of anal pre-cancerous lesions and cancer in people living with HIV-1 infection in the Southeastern U.S

Abstract: Background Anal cancer is rare in the general population in both genders in the US, but an increased incidence of anal cáncer (AC) has been reported among people living with HIV-1 infection (PLWH) and little is known among the population in South US. Methods In a retrospective study design, electronic health records from 2006 to 2018 were reviewed in a HIV clinical cohort at the University of Alabama at Birmingham. Associations of demographic, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Consistent with previous studies, the prevalence of anal cancer was higher among MLWH compared with their non‐HIV counterparts, and this association was stronger in the younger age group 13,14 (nearly 500 times higher in the younger age group vs 36 times higher in the older age group). These findings suggest that the burden of anal cancer is of much greater magnitude than previously described in PLWH, although most prior studies have reported hazard or risk ratios rather than prevalence ratios, as we do in this study 14,24,25 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous studies, the prevalence of anal cancer was higher among MLWH compared with their non‐HIV counterparts, and this association was stronger in the younger age group 13,14 (nearly 500 times higher in the younger age group vs 36 times higher in the older age group). These findings suggest that the burden of anal cancer is of much greater magnitude than previously described in PLWH, although most prior studies have reported hazard or risk ratios rather than prevalence ratios, as we do in this study 14,24,25 …”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest that the burden of anal cancer is of much greater magnitude than previously described in PLWH, although most prior studies have reported hazard or risk ratios rather than prevalence ratios, as we do in this study. 14,24,25 Our findings also showed variations in excess cancer prevalence by HIV symptomatic status and across cancer sites. MLWH experienced higher cancer prevalence than men without HIV for most cancer types, whether they were in the symptomatic or asymptomatic groups.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…9 Furthermore, previous evidence suggests that HR-HPV infection, such as HPV-16, is implicated in nearly 90% of anal cancer cases. 10 , 11 All these factors have made anal cancer an increasingly concerning but preventable malignancy. Other risk factors for anal cancer include immunosuppression due to solid-organ transplantation, history of vulvar or cervical HSIL or cancer, history of receptive anal intercourse, history of genital warts, anal fissures or fistulas and smoking.…”
Section: Introductionmentioning
confidence: 99%